2010
DOI: 10.1002/jbmr.9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stretching induces osteoprotegerin in differentiating C2C12 precursor cells through noncanonical Wnt Pathways

Abstract: Mechanical loading is known to be important for maintaining the formation and resorption rates of bone. To study the mechanisms by which mechanical loading regulates osteogenesis, we investigated the role of the Wnt pathway in C2C12 cells committed to osteogenic differentiation in response to cyclic mechanical stretching. Osteoprotegerin (OPG) acts as a decoy receptor for RANKL to inhibit osteoclastogenesis and resorption of bone. Our results demonstrate that stretching leads to a sustained increase in OPG exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 70 publications
2
19
0
Order By: Relevance
“…The extracellular-related kinase (ERK) and p38 kinase pathways are strong candidates for this activity since previous work has shown that mechanical stimulation induces a rapid and transient change in both kinase activities in C2C12 and osteoblast-like cells [41][42][43]. Also, the Wnt signalling pathway is involved in the response of bone-like cells to mechanical loading [44] and is also active during osteogenic differentiation of C2C12 cells [45][46][47]. Consistent with these findings, our Western blot data suggest that low-frequency mechanical stimulation following BMP-2 priming may act primarily through ERK and -catenin (Wnt) signalling.…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular-related kinase (ERK) and p38 kinase pathways are strong candidates for this activity since previous work has shown that mechanical stimulation induces a rapid and transient change in both kinase activities in C2C12 and osteoblast-like cells [41][42][43]. Also, the Wnt signalling pathway is involved in the response of bone-like cells to mechanical loading [44] and is also active during osteogenic differentiation of C2C12 cells [45][46][47]. Consistent with these findings, our Western blot data suggest that low-frequency mechanical stimulation following BMP-2 priming may act primarily through ERK and -catenin (Wnt) signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prototypical agonist for noncanonical Wnt-signaling Wnt5a was dramatically enhanced by both differentiation and TSH. Wnt5a is known to increase bone mass and to drive OPG production, mainly from mature osteoblasts (24).…”
Section: Discussionmentioning
confidence: 99%
“…Pluripotent mesenchymal precursor cell line C2C12 was utilized, which has been widely used as an in vitro model system to assess osteoblast differentiation [33], [34]. Furthermore, we explored the underlying mechanisms of cyclin G2 to suppress estrogen-mediated osteogenesis.…”
Section: Introductionmentioning
confidence: 99%